2021
DOI: 10.1177/1558689821989834
|View full text |Cite
|
Sign up to set email alerts
|

A Vignette-Based Transformative Multiphase Mixed Methods Interventional Study Featuring Venn Diagram Joint Displays: Financial Education With Hong Kong Early Adolescent Ethnic Minority Students

Abstract: Despite great interest in the transformative mixed methods, an example of using vignettes in a multiphase mixed methods interventional study has been lacking. This study investigates the social justice problem of poverty in the context of financial education with Hong Kong early adolescent ethnic minority students. The discussion contributes to the field of mixed methods research by demonstrating the use of a vignette-based methodology as a tool for integration, representation, and utilization of participant v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Parental financial socialization is part of informal financial socialization, and finance-related norms and beliefs are usually passed and shared among family members in unstructured ways (e.g., parents passing along partially true information or letting the offspring discover principles and rules from observations and hands-on experiences; Klontz et al, 2015). Specific to the associations from parental financial socialization to financial enabling, we have stated in the introduction section that sharing and giving financial resources is one of the major topics in parental financial socialization (LeBaron-Black, Curran, et al, 2022;Ling & Pang, 2022). However, in teaching this principle to their children, parents may have ignored the importance of teaching children to avoid over-giving.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parental financial socialization is part of informal financial socialization, and finance-related norms and beliefs are usually passed and shared among family members in unstructured ways (e.g., parents passing along partially true information or letting the offspring discover principles and rules from observations and hands-on experiences; Klontz et al, 2015). Specific to the associations from parental financial socialization to financial enabling, we have stated in the introduction section that sharing and giving financial resources is one of the major topics in parental financial socialization (LeBaron-Black, Curran, et al, 2022;Ling & Pang, 2022). However, in teaching this principle to their children, parents may have ignored the importance of teaching children to avoid over-giving.…”
Section: Discussionmentioning
confidence: 99%
“…However, according to a recently developed parental financial socialization scale based on a U.S. sample (LeBaron-Black, Curran, et al, 2022, which was also used in the present study), researchers found that parents also provided their offspring the lived experiences of giving and sharing money ("My parents encouraged me to put a certain percentage of my money away for something like savings or donations"). For Hong Kong young adults, giving and sharing money is a norm in Chinse families, and family members usually sacrifice personal financial well-being for the sake of others (Ling & Pang, 2022). Thus, it may be expected for Hong Kong young adults to learn financial enabling (i.e., giving money to others even though one cannot afford it) from parents.…”
Section: Parental Financial Socialization Financial Behaviors and Wel...mentioning
confidence: 99%
“…Although quantitizing data remains a popular approach, mixed methods researchers will continue to be interested in unique and multilevel approaches to integration. Ling and Pang (2022), who transformed both qualitative and quantitative data into narrative vignettes, and Youngs and Piggot-Irvine (2012) who employed three types of triangulation, provide such example integration practices. Future research should engage in more visual and arts-based approaches to integration.…”
Section: Contributions To Educational Research and Mixed-methods Rese...mentioning
confidence: 99%
“…This study demonstrated how network analysis can be used to validate findings from earlier phases of a mixed methods study. Ling and Pang (2022) demonstrated qualitizing integration. They created vignettes from qualitative and quantitative data during their evaluation of a financial education program for ethnic minority students in Hong Kong.…”
Section: Applying Various Forms Of Integration To Merge or Transform ...mentioning
confidence: 96%
“…Another variation has included the use of photos (Peroff et al, 2020; NeMoyer et al, 2020). Others have moved away from a matrix or table style into other creative formats, e.g., as circular joint display (Bustamante, 2019), mapping (Teixeira, 2016; Kieber-Emmons et al, 2022), figures (Takeuchi et al, 2021), and Venn diagrams (Ling & Pang, 2021). Tajima and Fetters (2021) developed a variation for comparing two groups in an interventional study that featured in their joint displays pre- and post-intervention quantitative, qualitative, and MM interpretations as meta-inferences.…”
Section: Introductionmentioning
confidence: 99%